Oligohydramnios : A risk of adverse perinatal outcomes - Yee Yee, Kyaing (Malaysian Medical Association, 2023)
Introduction: Oligohydramnios is diagnosed when amniotic fluid index is less than 5. The incidence is between 1% and 4.4%. Although there are various maternal, fetal and placental contributory factors, the cause in the majority of cases is unknown. Most oligohydramnios cases warrant obstetric intervention. Case Description: A 22-year-old, Gravida 3 Parity 1+1 lady was diagnosed to have gestational diabetes at 15 weeks of gestation, which was well controlled with diet throughout pregnancy. At 34 weeks of gestation, ultrasound examination showed oligohydramnios. Ultrasound assessment confirmed both fetal kidneys were present, and bladder was seen. End diastolic flow was present in umbilical doppler and estimated fetal weight was 2.07 kilograms. After the administration of dexamethasone for fetal lung maturity, induction of labour was started with Cook’s balloon catheter. After 5 hours, cardiotocograph showed fetal tachycardia with a non-reassuring tracing. The emergency lower segment caesarean section was performed and a baby of 2.07 kilograms was born with Apgar score 1 in 1 minute and 5 minutes. Umbilical cord blood pH of artery and vein were 7.35 and 7.338 respectively. The baby passed away the next day. Discussion: Pregnancy with oligohydramnios have a higher chance of g induction of labour which is beneficial. Pregnancies complicated with only oligohydramnios without underlying disorders may not be associated with adverse neonatal outcomes. But there is evidence that oligohydramnios cases with underlying disorders, their labours are likely to be associated with abnormal cardiotocographs, a higher rate of emergency caesarean sections and adverse neonatal outcomes.